Terminal Sliding Mode Control Based on New Quasi-Sliding Mode Function for Two Tanks Interacting System - Pham, Thanh Tùng; Nguyen, Chí Ngôn (Journal of Technical Education Science, 2022)
In this paper, a terminal sliding control based on a new quasi-sliding mode function is designed to control a liquid level in two tanks interacting system with external disturbance and uncertainty. This system is always in great demand in the chemical industry, petrochemical refining, water treatment, power generation, construction material production, food processing, automatic liquid dispensing and replenishment devices. The terminal sliding mode control (TSMC) schemes not only ensure that the system states arrive at the equilibrium point in a finite time but also offer some attractive properties, such as their fast response and higher precision than traditional sliding mode control. The new quasi-sliding mode function will eliminate high frequency oscillations phenomenon around a sliding surface (also known as chattering) of the sliding mode control. This phenomenon causes instability in the system, the power driver circuits are susceptible to overheating, resulting in damage. Simulation results in MATLAB/Simulink show that the proposed method is suitable to control the liquid level’s position of the two tanks interacting system with without the percent overshoot, the steady state error is eliminated, the settling time is 0.8518(s), the rising time achieves 0.4054(s), and the chattering phenomenon is eliminated.